Os jogos digitais na perspectiva da Ciência da Informação: narrativas interativas por meio de ludemas. - Jose Ricardo da Silva Neto (2023)
Digital games have been gaining more and more public, having, in recent years, computed a significant increase in the number of players and reaching, in 2022, the mark of 74.5% of the Brazilian population. In order to characterize this type of game as an entertainment media from the perspective of Information Science, bringing it closer to the definition of document, we used, among others, the concepts of ludema - as an update component, which contains in itself the narrative, the rules and the challenges of the game - and the concept of protoinformation, - understood as potential information. To this end, an integrative bibliographic review was carried out in order to support the elaboration of reflections on the relationship between the user and the information from the digital game. The theoretical development concluded that the digital game is a document whose functioning is ordered by the execution of ludemas. It was found that the ludema fulfills an elementary function for research on the information and content of digital games in the field of Information Science, by describing the functioning of games and the way information is presented to the player, serving as a basis for new research aimed at understanding digital games and other platforms dedicated to an informational interactive dynamic. At the same time, the results of the present investigation suggested interesting possibilities for the extrapolation of the concept of ludema as an informational artifact to other fields outside the field of games sciences.